Transcriptome Sequencing and Development of Novel Genic SSR Markers From Pistacia vera L. - Karcι, Harun; Paizila, Aibibula; Topçu, Hayat; Ilikçioğlu, Ertuğrul; Kafkas, Salih (Frontiers in Genetics, 2020)
In this study, we aimed to develop novel genic simple sequence repeat (eSSR) markers and to study phylogenetic relationship among Pistacia species. Transcriptome sequencing was performed in different tissues of Siirt and Atlı cultivars of pistachio (P. vera). A total of 37.5 Gb data was used in the assembly. The number of total contig and unigene was calculated as 98,831 and the length of N50 was 1,333 bp after assembly. A total of 14,308 di-, tri-, tetra-, penta- and hexa-nucleotide SSR motifs (4-17) were detected and the most abundant SSR repeat types were tri-nucleotide (29.54%), di-nucleotide (24.06%), hexa-nucleotide (20.67%), penta-nucleotide (18.88%) and tetra-nucleotide (6.85%), respectively. Overall 250 primer pairs were designed randomly and tested in eight Pistacia species for amplification. Of them, 233 were generated PCR products in at least one of the Pistacia species. A total of 55 primer pairs that had amplifications in all tested Pistacia species were used to characterize 11 P. vera cultivars and 78 wild Pistacia genotypes belonging to nine Pistacia species (P. khinjuk, P. eurycarpa, P. atlantica, P. mutica, P. integerrima, P. chinensis, P. terebinthus, P. palaestina and P. lentiscus). A total of 434 alleles were generated from 55 polymorphic eSSR loci with an average of 7.89 alleles per locus. A mean number of effective allele was 3.40 per locus. Polymorphism information content (PIC) was 0.61, while observed (Ho) and expected heterozygosity (He) values were 0.39 and 0.65, respectively. UPGMA (unweighted pair group method with arithmetic averages) and STRUCTURE analysis divided 89 Pistacia genotypes into seven populations. The closest species to P. vera was P. khinjuk. P. eurycarpa was closer P. atlantica than P. khinjuk. P. atlantica-P. mutica and P. terebinthus-P. palaestina pairs of species were not clearly separated from each other and they were suggested as the same species. The present study demonstrated that eSSR markers can be used in the characterization and phylogenetic analysis of Pistacia species and cultivars as well as genetic linkage mapping and QTL (quantitative trait locus) analysis.